GQTL: A Web Application for QTL Analysis Using the Collaborative Cross Mouse Genetic Reference Population. Issue 8 (1st August 2018) - Konganti, Kranti; Ehrlich, Andre; Rusyn, Ivan; Threadgill, David W
Abstract: Multi-parental recombinant inbred populations, such as the Collaborative Cross (CC) mouse genetic reference population, are increasingly being used for analysis of quantitative trait loci (QTL). However specialized analytic software for these complex populations is typically built in R that works only on command-line, which limits the utility of these powerful resources for many users. To overcome analytic limitations, we developed gQTL, a web accessible, simple graphical user interface application based on the DOQTL platform in R to perform QTL mapping using data from CC mice.